Globalisation, Societies and Education Special Issue: Student activism, translocality, and social justice (Journal of Student Affairs in Africa, 2022)
In many countries and universities, students engage in activities to promote socialjustice through inclusion, diversity, epistemic freedom and decolonisation, payingrenewed attention to intersectionalities of race/ethnicity, class, gender and sexuality. Inthis special issue, we seek to focus on the translocal dimensions of student activism forequality and greater social justice. We understand ‘activism’ quite broadly to includestudent-led activities – ranging from small-scale mundane initiatives to large-scaleprotest events – that aim to change everyday life, practices or norms at the universityand beyond. Students’ activist engagement is often shaped in and through translocal/transnational/international/global spaces in which geo-political imaginaries, academictheories, actionable knowledge or symbols, hashtags, materiality and people circulateand move across socio-political contexts. Struggles are connected across multiple scales,and partially common worlds and horizons are created.